1998
DOI: 10.1046/j.1365-2516.1998.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Heamoperitoneum caused by heamorrhagic corpus luteum in a patient with type 3 von Willebrand’s disease

Abstract: In female patients affected by congenital coagulation disorders haemorrhagic corpus luteum must be considered for the differential diagnosis of acute abdomen. We report the complication in a 22-year-old woman with type 3 von Willebrand's disease who presented with abdominal pain and haemorrhagic shock. Along with adequate factor VIII replacement therapy oral contraceptive treatment is the key for the management of this potentially life-threatening complication and the long-term prevention of future bleeding ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Haemorrhagic ovarian cysts have also been reported in women with afibrinogenemia, factor X deficiency, factor XIII deficiency, platelet defects or in women who are haemophilia carriers [18]. Acutely, surgery, tranexamic acid and clotting factor replacement have been used to manage haemorrhagic ovarian cysts [19][20][21]. Oral contraceptives, which suppress ovulation and may increase clotting factors, have been used to prevent recurrences [21][22][23].…”
Section: Other Gynaecological Bleedingmentioning
confidence: 99%
“…Haemorrhagic ovarian cysts have also been reported in women with afibrinogenemia, factor X deficiency, factor XIII deficiency, platelet defects or in women who are haemophilia carriers [18]. Acutely, surgery, tranexamic acid and clotting factor replacement have been used to manage haemorrhagic ovarian cysts [19][20][21]. Oral contraceptives, which suppress ovulation and may increase clotting factors, have been used to prevent recurrences [21][22][23].…”
Section: Other Gynaecological Bleedingmentioning
confidence: 99%
“…There are multiple case reports of women with VWD experiencing hemorrhagic ovarian cysts (11,10,(69)(70)(71)(72)(73). Silwer reported that 9 of 136 women with VWD (6.8%) experienced this problem (19).…”
Section: Other Gynecologic Problemsmentioning
confidence: 99%
“…In a CDC survey of 102 women with VWD, 52% reported a history of ovarian cysts compared with 22% of control subjects (15). Surgical therapy, tranexamic acid, and factor replacement have been used acutely to manage hemorrhagic ovarian cysts (11,69,72). Oral contraceptives, which increase coagulation factors while suppressing ovulation, have been used to prevent recurrences (69,70,73).…”
Section: Other Gynecologic Problemsmentioning
confidence: 99%
“…Corpus luteum hemorrhage may go unnoticed in healthy women; however, corpus luteum hemorrhage may lead to life‐threatening intraperitoneal hemorrhage in women with bleeding disorders 1 . Corpus luteum rupture resulting in hemoperitoneum has been described in women with various bleeding disorders, such as hemophilia, afibrinogenemia, von Willebrand disease, and factor X, VII and V deficiencies 2–5 . Nevertheless, few reports have described corpus luteum hemorrhage in patients with aplastic anemia (AA) 6,7 .…”
Section: Introductionmentioning
confidence: 99%